Volatility Transmission and Market Connectivity of Metals and Energy Commodities: Insights from the Spillover Index - Tessmann, Mathias; Carrasco-Gutierrez, Carlos; Khodr, Omar; Magalhães, Luiz Augusto; Passos, Marcelo (International Journal of Energy Economics and Policy, 2024)
This paper explores the interconnections between metal and energy commodities by assessing the transmission of volatility within their futures markets. Achieved through the spillover index, the analysis reveals the impact of shocks on asset pairs—highlighting which assets absorb and transmit volatility, thereby explaining market connectivity. The dataset covers a period of twenty years of daily closing prices from the London Metals Exchange for a range of commodities. The Diebold and Yilmaz (2012) index, enriched by Baruník and Krehlík (2018) was used to reflect the changes in trends. The results obtained provide insights into market connectivity and the propagation of volatility during periods of economic distress. In this context, following the 2008 crisis, precious metals exhibited significant interconnectivity, with the emergence of Silver’s vulnerability along with Gold’s volatility tied to pre-crisis returns. Furthermore, copper’s volatility reflects conditional correlations with market stock prices and other commodities particularly during economic downturns.